Composite Strain Hardening Properties of High Performance Hybrid Fibre Reinforced Concrete - Vikram Jothi Jayakumar; Sivakumar Anandan (Advances in Civil Engineering)
Hybrid fibres addition in concrete proved to be a promising method to improve the composite mechanical properties of the cementitious system. Fibre combinations involving different fibre lengths and moduli were added in high strength slag based concrete to evaluate the strain hardening properties. Influence of hybrid fibres consisting of steel and polypropylene fibres added in slag based cementitious system (50% CRL) was explored. Effects of hybrid fibre addition at optimum volume fraction of 2% of steel fibres and 0.5% of PP fibres (long and short steel fibre combinations) were observed in improving the postcrack strength properties of concrete. Test results also indicated that the hybrid steel fibre additions in slag based concrete consisting of short steel and polypropylene (PP) fibres exhibited a the highest compressive strength of 48.56 MPa. Comparative analysis on the performance of monofibre concrete consisting of steel and PP fibres had shown lower residual strength compared to hybrid fibre combinations. Hybrid fibres consisting of long steel-PP fibres potentially improved the absolute and residual toughness properties of concrete composite up to a maximum of 94.38% compared to monofibre concrete. In addition, the relative performance levels of different hybrid fibres in improving the matrix strain hardening, postcrack toughness, and residual strength capacity of slag based concretes were evaluated systematically.